Study of the Effect of Bottom Ash and Palm Shell Kernel as Materials in Bricks - Muhammad Nur Haneef Mohd Yusoff; Mohamad Luthfi Ahmad Jeni; Hilmi Kosnin (Progress in Engineering Application and Technology, 2024)
This study delves into the practicality and effectiveness of incorporating bottom ash and palm shell kernel as partial substitutes for fine aggregates in cement brick production. The investigation explores proportions ranging from 10% to 20% for both materials, following a preliminary treatment involving drying under sunlight and meticulous sieving. The blending process will adhere to a 1:6 ratio relative to aggregates. The modified brick specimens will undergo thorough curing, followed by a battery of tests, including assessments of compressive strength and water absorption. The main goal is to evaluate how bottom ash and palm shell kernel impact the performance of cement bricks, aiming to either enhance or at least maintain their quality. Concurrently, the study seeks to offer an eco-friendly alternative to traditional fine aggregates, contributing to sustainable construction practices. The research anticipates providing valuable insights into utilizing industrial by-products for construction materials, fostering a dialogue on environmentally conscious and resource-efficient construction. The expected outcomes aim to advance sustainable building practices by promoting the use of such by-products in construction